Validation of the portuguese version of the Questionnaire on Eating and Weight Patterns: revised (QEWP-R) for the screening of binge eating disorder - Borges,Maria Beatriz Ferrari (2005)
OBJECTIVE: The present paper describes the validation of the Questionnaire on Eating and Weight Patterns-Revised (QEWP-R) designed for the diagnosis of binge eating disorder (BED) and sub-clinical binge eating. METHODS: 89 overweight women seeking treatment for binge eating and/or obesity were assessed with the Portuguese version of the Questionnaire of Eating and Weight Patterns and were, subsequently, interviewed with the eating disorders module of the Structured Clinical Interview for DSM-IV (SCID-I/P). Rates of binge eating disorder and sub-clinical cases of binge eating obtained with the Questionnaire on Eating and Weight Patterns-Revised were then compared to those obtained with the Structured Clinical Interview for DSM-IV. RESULTS: In the identification of binge eating, irrespective of the presence of all criteria for binge eating disorder the QEWP-R Questionnaire on Eating and Weight Patterns-Revised yielded a sensitivity value of 0.88, a specificity value of 0.63 and a positive predictive value of 0.825. Rates for the identification of the full syndrome of binge eating disorder were: sensitivity value of 0.548, a specificity value of 0.8 and a positive predictive value of 0.793. CONCLUSIONS: The Questionnaire on Eating and Weight Patterns-Revised can be useful in a first-step screening procedure to identify probable cases of binge eating. It can be useful as a screening tool and as a first step of clinical assessment of patients seeking treatment for binge eating and/or obesity.